Characterisation of gold ores by X-ray computed tomography - Part 2: Applications to the determination of gold particle size and distribution - Dominy, Simon; Platten, I.; Howard, L.; Elangovan, P.; Armstrong, R.; Minnitt, R.; Abel, R. (2011)
For any gold deposit-based geometallurgical study, the collection and processing of representative samples for gold grade and recovery tests is critical. Sampling protocols should be designed to suit the style of orebody in question. The proportion and size of gold particles has a direct impact on the effectiveness of sampling protocols and metallurgical recovery processes employed. Studies focussing on ore mineralogy and gold particle deportment, size and distribution are required. Key issues are the presence of gold particle clustering (important for sampling optimisation) and proportion of coarse versus fine to refractory gold. X-ray computed tomography (CT) is a radiographic technique that produces high-resolution 3D computerised models of objects based on density distribution. The 'virtual' specimens are made up of voxels, the 3D equivalent of pixels each assigned a grey value based on X-ray absorption. This paper presents the results of recent research on the imaging of in situ gold particles in a coarse gold-bearing ore. The technique shows promise as a rapid non-destructive method for preliminary characterisation to facilitate more detailed studies. Early and rapid gold particle determination enables sampling protocol optimisation and metallurgical recovery parameters to be defined prior to detailed feasibility studies.